Model Pendekatan dan Supervisi - Khoirul Imam; Arfan Hamdani; Meti Fatimah (Lembaga Yasin AlSys, 2026)
Islamic educational supervision is a process of professional development that is oriented not only toward improving the quality of learning but also toward developing teachers’ character and spirituality. However, the implementation of supervision that integrates modern approaches with Islamic values still requires conceptual strengthening. This study aims to describe supervisory models and approaches relevant to the context of Islamic education. The study employed a qualitative approach through a literature review of traditional, clinical, developmental, humanistic, collaborative, and Islamic values-based supervision concepts, as well as the ideas of Carl D. Glickman, Carl Rogers, and Morris L. Cogan. The data were analyzed descriptively and conceptually to identify the characteristics, relevance, and integration of each supervisory model and approach. The findings indicate that Glickman’s ideas emphasize the importance of adapting supervisory approaches to teachers’ developmental levels, Rogers prioritizes empathetic relationships, while Cogan offers a systematic clinical supervision framework for improving the quality of learning. From an Islamic perspective, the values of consultation, exemplary conduct, and compassion constitute important foundations for the implementation of supervision. The integration of modern supervisory models and Islamic values produces an approach that is more humanistic, adaptive, collaborative, and oriented toward developing teachers’ professional competence and moral character. This study concludes that Islamic educational supervision functions not only as an evaluation instrument but also as a means of comprehensive and sustainable professional and spiritual development. These findings contribute to the development of an Islamic educational supervision framework that is appropriate to teachers’ needs and the characteristics of Islamic educational institutions.